PETM in a shallow marine environment: benthic foraminiferal Turnover and echinoid bloom (Sidi Nasseur, Tunisia) - Stassen, Peter; Dupuis, Christian; Magioncalda, Roberto; Schulte, Peter; Steurbaut, Etienne; Yans, Johan; Speijer, Robert P. (Anuário do Instituto de Geociências, 2006)
Abstract